Shot-by-shot stability of the discharge produced plasmas in suitably shaped capillaries. (1st April 2023) - Arjmand, S.; Anania, M.P.; Biagioni, A.; Ferrario, M.; Del Franco, M.; Galletti, M.; Lollo, V.; Pellegrini, D.; Pompili, R.; Zigler, A.
Abstract: Compact accelerator machines are capable of producing accelerating gradients in the GV/m scale, which is significantly higher than the MV/m scale of conventional machines. As accelerators are widely used in many fields, such as industrial, research institutes, and medical applications, the development of these machines will undoubtedly have a profound impact on people's daily lives. SPARC_LAB, a test facility at INFN-LNF (Laboratori Nazionali di Frascati), is focused on enhancing particle accelerator research infrastructure using innovative plasma acceleration concepts. Within SPARC_LAB, we utilize plasma-filled capillaries with lengths of up to tens of centimeters. However, the plasma formation process is critical to ensure proper oversight of the plasma properties, which subsequently affects the dynamics of the electron bunch to be accelerated. One of the most critical points that significantly affects the properties of the electron beam passing through the plasma source is the shot-by-shot stability of the plasma density along the longitudinal dimension of the plasma-discharge capillary. Therefore, this paper aims to investigate the shot-by-shot stability of the plasma density during discharge, contributing to further advancements in the field of plasma acceleration.